Stretching the Function of Innate Immune Cells - Orsini, Erica M.; Perelas, Apostolos; Southern, Brian D.; Grove, Lisa M.; Olman, Mitchell A.; Scheraga, Rachel G. (Frontiers in Immunology, 2021)
The importance of innate immune cells to sense and respond to their physical environment is becoming increasingly recognized. Innate immune cells (e.g. macrophages and neutrophils) are able to receive mechanical signals through several mechanisms. In this review, we discuss the role of mechanosensitive ion channels, such as Piezo1 and transient receptor potential vanilloid 4 (TRPV4), and cell adhesion molecules, such as integrins, selectins, and cadherins in biology and human disease. Furthermore, we explain that these mechanical stimuli activate intracellular signaling pathways, such as MAPK (p38, JNK), YAP/TAZ, EDN1, NF-kB, and HIF-1α, to induce protein conformation changes and modulate gene expression to drive cellular function. Understanding the mechanisms by which immune cells interpret mechanosensitive information presents potential targets to treat human disease. Important areas of future study in this area include autoimmune, allergic, infectious, and malignant conditions.